2021
DOI: 10.3389/fphar.2021.626510
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir Inhibits Tubulointerstitial Fibrosis in Obstructed Kidneys

Abstract: Aim: Kidney impairment is observed in patients with COVID-19. The effect of anti-COVID-19 agent remdesivir on kidneys is currently unknown. We aimed to determine the effect of remdesivir on renal fibrosis and its downstream mechanisms.Methods: Remdesivir and its active nucleoside metabolite GS-441524 were used to treat TGF-β stimulated renal fibroblasts (NRK-49F) and human renal epithelial (HK2) cells. Vehicle or remdesivir were given by intraperitoneal injection or renal injection through the left ureter in u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Moreover, GS‐441524 at a concentration as high as 50 μM was required to produce alteration in the in vitro antigen‐induced memory T cell proliferation 38 . Consistent with this, concentrations of GS‐441524 in the range between 10 and 100 µM were necessary to inhibit proliferation of NRK‐49F cells and HK‐2 cells, derived from rat and human kidneys, after stimulation with transforming growth factor‐β, whereas marked inhibition of the protein expression of fibrotic markers such as fibronectin was detected at a concentration of this nucleoside analog of 10 µM 39 …”
Section: Safety and Toxicitymentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, GS‐441524 at a concentration as high as 50 μM was required to produce alteration in the in vitro antigen‐induced memory T cell proliferation 38 . Consistent with this, concentrations of GS‐441524 in the range between 10 and 100 µM were necessary to inhibit proliferation of NRK‐49F cells and HK‐2 cells, derived from rat and human kidneys, after stimulation with transforming growth factor‐β, whereas marked inhibition of the protein expression of fibrotic markers such as fibronectin was detected at a concentration of this nucleoside analog of 10 µM 39 …”
Section: Safety and Toxicitymentioning
confidence: 53%
“… 38 Consistent with this, concentrations of GS‐441524 in the range between 10 and 100 µM were necessary to inhibit proliferation of NRK‐49F cells and HK‐2 cells, derived from rat and human kidneys, after stimulation with transforming growth factor‐β, whereas marked inhibition of the protein expression of fibrotic markers such as fibronectin was detected at a concentration of this nucleoside analog of 10 µM. 39 …”
Section: Safety and Toxicitymentioning
confidence: 65%
“… 12 On the other hand, animal studies demonstrated potential, beneficial, renal effects in reversing obstructive renal fibrosis. 13 Of note, such cohort of patients with chronic kidney disease at significant risks of acquisition and complications of COVID‐19 disease as highlighted from multiple observational studies. 14 Such circumstances require developing management strategies for such population including careful evaluation, trials of therapy then sharing the experience.…”
Section: Discussionmentioning
confidence: 99%
“…before UUO operation. UUO model was established by ligation of the left ureter as described previously [ 20 , 21 ]. Mice were randomly divided into four groups: 1) Sham/DMSO ( n = 9), 2) Sham/Tan-I ( n = 8), 3) UUO/DMSO ( n = 8), and 4) UUO/Tan-I ( n = 11) group.…”
Section: Methodsmentioning
confidence: 99%
“…Normal rat kidney 49F (NRK-49F) cells, a rat kidney interstitial fibroblast cell line, were purchased from national infrastructure of cell line resource, Chinese academy of medical sciences. NRK-49F cells were cultured in DMEM/F12 medium containing 10% fetal bovine serum and 0.5% penicillin and streptomycin in an atmosphere of 5% CO2 and 95% air at 37 °C according to previous studies [ 20 , 21 ]. To study the anti-fibrotic effect of Tan I, NRK-49F cells were seeded in 6-well plates to 40–50% confluence and were starved with DMEM/F12 medium containing 0.5% fetal bovine serum overnight before the experiment.…”
Section: Methodsmentioning
confidence: 99%